Analysis of cassava chip image characterization during drying process. Issue 1 (November 2021) - Sandra,; Hendrawan, Y; Damayanti, R; Perdana, L P R
Abstract: Monitoring method during food processing is an indispensable activity in the industry of food processing. A digital image processing technique is one of the methods to process images into information in the form of product physical condition. This study aimed to monitor the changes in cassava chips image characteristics through the images along the drying process. The image characteristic i.e covered color, texture, and area. The images were captured by using Webcam type Logitech C525 8.0 megapixel autofocus per minute. Then, the result of these images was processed to get color data of R, G, B, H, S, I, L, a*, b* and the texture i.e. energy, homogeneity, contrast, entropy, and to identify chips size was processed by the number of pixels of the image. While the data about the mass changes along the drying process were taken per minute from a digital scale. The results of this study showed that the length of drying made the value of R, G, B, H and I decreased, but the value of S contrastively increased. The area or the number of image pixels declined dramatically in 1 hour of drying, later (after one hour of drying) the decline was almost zero.